Heavy Metals in some Malaysian Mosses - Lee, Chnoong Kheng; Low, Kun She; Phoon, Azhar; Loi, Patrick Suok Tee (1983)
Sixty-five moss samples were collected randomly from areas in and around Kuala Lumpur and analysed for Zn. Pb, Cd, Cu, Ni, Fe and Mn. A definite trend was observed for the variation of Pb concentration in mosses. The variations for the other metals were, however, not clearly defined. The background values for these metals were generally comparable to previously reported values except Fe which was high. Correlation studies among the metals were performed and the results indicated positive significant -correlations among Pb, Cd, Cu, Fe and Mn. The suitability of using mosses as pollution indicators is discussed